Les tableaux animés de la production Pathé (Cinéma & Cie. Film and Media Studies Journal, 2013)
In this essay, the author discovers an intriguing anomaly in Pathé’s early catalogues – the presence and yet absence of “tableaux vivants.” From 1897 until 1907, Pathé Frères produced no fewer than about fifty films considering in realizations of famous paintings. Although numerous and impressive, these living pictures set on screen and in motion are unmentioned in the promotional documents of the period. In the Pathé catalogues, these “re-animated paintings” do not have their own category; instead, they are scattered throughout other “genres” of film. Pathé's description of them also also changes over time - the pictorial references seem to disappear. This growing silence may be a result of the legal climate of the time, shaken by the first copyright complaints in the film and phonograph industries. Or, it may be  related to the way realistic and historical paintings of that time were taken for accurate documents and not for an artist’s vision. But, it may also be the new “era of reproductive technology” that freed works (intended to be reinterpreted through all media) from any “original” identity. In any event, this “secret” seems to hold the key to Pathé Frères’ early success: a cinema production conceived as a cinema of reproduction.